A Fuzzy Multi-Criteria Approach for Selecting Open-Source ERP Systems in SMEs Using Fuzzy AHP and TOPSIS - Dana Marsetiya Utama; Muhammad Faisal Ibrahim; Ahmed Nedal Abid Al Kareem Jabari (Jurnal Optimasi Sistem Industri, 2024)
In a rapidly growing and competitive business era, selecting an open-source Enterprise Resource Planning (ERP) system is a critical step to support the eﬃciency and eﬀectiveness of company operations. This research aims to propose an innovative methodology by integrating the fuzzy Analytical Hierarchy Process (fuzzy AHP) and fuzzy Technique for Order Preference by Similarity to the Ideal Solution (fuzzy TOPSIS) to improve the open-source ERP selection process. The method involves eight criteria and 26 sub-criteria to comprehensively evaluate 11 open-source ERP alternatives, speciﬁcally for SMEs in the transportation services sector in Indonesia. System quality has been identiﬁed as a critical factor in the selection of an open-source ERP system, with particular emphasis on aspects such as security and reliability. These sub-criteria are considered the most inﬂuential in determining the suitability of a system. The analysis further indicates that the 10th ERP alternative as the best choice, consistently outperforming others in meeting the deﬁned criteria. Additionally, sensitivity analysis conﬁrmed the robustness of this choice, demonstrating its stability and eﬀectiveness despite changes in criteria weights. Beyond its practical implications for SMEs, this research contributes a versatile evaluation framework that can be adapted to other industries seeking eﬀective ERP solutions. The ﬁndings emphasize the importance of structured decision-making in technology adoption, oﬀering comprehensive and reliable guidance for organizations aiming to optimize their operations through open-source ERP systems. This study not only bridges a critical gap in ERP selection for SMEs but also establishes a methodological foundation for future research and applications across diverse industry sectors.